Lipoprotein(a), apolipoprotein E genotype, and risk of Alzheimer's disease. Issue 6 (1st June 2002) - Solfrizzi, V; Panza, F; D'Introno, A; Colacicco, A M; Capurso, C; Basile, A M; Capurso, A
Abstract : Objectives: To explore the possible role of serum lipoprotein(a) (Lp(a)), apolipoprotein E polymorphism, and total cholesterol (TC) serum concentrations in Alzheimer's disease (AD). Methods: Lp(a) serum concentrations, apolipoprotein E genotypes, and TC serum concentrations were determined in 61 patients with a diagnosis of probable AD and in 63 healthy unrelated age matched controls. Genomic DNA was obtained and amplified by polymerase chain reaction and apolipoprotein E genotypes were defined following a previously described procedure. Results: Lp(a) serum concentrations were significantly associated in a non-linear relation with an increased risk for AD, independently of apolipoprotein E genotypes and sex and dependent on age (truth association) and TC serum concentrations (spurious association). The effect of age adjusted for TC on the odds of having AD increased non-linearly with increasing Lp(a) serum concentrations, with a plateau between 70 and 355 mg/l (odds ratio 11.33). For Lp(a) serum concentrations ≥ 360 mg/l, the effect of age (≥ 72 years) was associated with a reduction in odds of having AD (odds ratio 0.15). Conclusion: It is suggested that increased Lp(a) serum concentrations, by increasing the risk for cerebrovascular disease, may have a role in determining clinical AD.